(3agQSJ JQGLe GdYdeGA hGdTYQGA GdPjf hQOJ CSeGDge aj TQM HGfJ SYGOs - (3YHO GdbGOQ Hf YeQ GdHZOGOj,J (B1093 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf , bGd(B: (3agPg agQSJ JQGLe GdYdeGA hGdTYQGA GdJi hbYJ ai TQM HGfJ SYGO s
(3Vef eLehY , JQJjHgG (B: (3ef U (B157 - (3U(B160s
(3HNW GHf GdeDda Yf NW CHjgs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B41 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B295s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B200 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1330s
Keywords: (3GdJGQjNs